2018
DOI: 10.1080/07448481.2018.1451869
|View full text |Cite
|
Sign up to set email alerts
|

College life is stressful today – Emerging stressors and depressive symptoms in college students

Abstract: This renewed look reinforced that tailored and sustained efforts are needed to address the continued prevalence of different stressors and associated depressive symptoms faced by college students on US campuses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
163
2
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(209 citation statements)
references
References 25 publications
11
163
2
8
Order By: Relevance
“…There are numerous reports that indicate that being a college student is stressful and that many students lack the coping resources necessary to navigate this normative transition (e.g., Acharya, Jin, & Collins, ; Cleary, Walter, & Jackson, ; The American College Health Association [ACHA], ; The Jed Foundation, The Jordan Matthew Porco Foundation, & The Partnership for Drug Free Kids, ). When the developmental instability characteristic of emerging adulthood (EA) is paired with inadequate coping, there is a high risk of poor college adjustment, academic failure, substance abuse, or significant psychopathology (Dennhardt & Murphy, ; Kadison & DiGeronimo, ).…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous reports that indicate that being a college student is stressful and that many students lack the coping resources necessary to navigate this normative transition (e.g., Acharya, Jin, & Collins, ; Cleary, Walter, & Jackson, ; The American College Health Association [ACHA], ; The Jed Foundation, The Jordan Matthew Porco Foundation, & The Partnership for Drug Free Kids, ). When the developmental instability characteristic of emerging adulthood (EA) is paired with inadequate coping, there is a high risk of poor college adjustment, academic failure, substance abuse, or significant psychopathology (Dennhardt & Murphy, ; Kadison & DiGeronimo, ).…”
Section: Introductionmentioning
confidence: 99%
“…Adjustment to college life is a stressful experience that is frequently associated with the development of depressive symptoms (Acharya, Jin, & Collins, 2018). Changes in sleeping habits, social activities, class workload, and living environment may all contribute to depressive symptoms among college students (Acharya et al, 2018). The association between sleep and mental health symptoms in college students supports the cognitive-energy model of sleep, which posits that sleep serves as a resource for managing emotional reactions to stress (Zohar, Tzischinsky, Epstein, & Lavie, 2005).…”
Section: T a B L E 1 Participant Demographic Information And Clinicalmentioning
confidence: 98%
“…The current study also found evidence indicating that inadequate sleep is associated with more symptoms of depression and anxiety. Adjustment to college life is a stressful experience that is frequently associated with the development of depressive symptoms (Acharya, Jin, & Collins, 2018). Changes in sleeping habits, social activities, class workload, and living environment may all contribute to depressive symptoms among college students (Acharya et al, 2018).…”
Section: T a B L E 1 Participant Demographic Information And Clinicalmentioning
confidence: 99%
“…Furthermore, adolescent depression was a strong predictor of mental disorders during adulthood [2]. For example, many investigators had reported that undergraduate students suffered from depression and are vulnerable to suicide attempt and completed suicide [3][4][5][6][7][8]. In a meta-analysis, Ibrahim also concluded that undergraduate students were more prone to depression with high prevalence [9].…”
Section: Introductionmentioning
confidence: 99%